Hydrothermal Synthesis and Structural Characterization of NiO/SnO2 Composites and Hydrogen Sensing Properties - Chao Wei; Bin Bo; Fengbo Tao; Yuncai Lu; Shudi Peng; Wei Song; Qu Zhou (Journal of Spectroscopy)
Pure SnO2 and NiO doped SnO2 nanostructures were successfully synthesized via a simple and environment-friendly hydrothermal method. X-ray powder diffraction (XRD), scanning electron microscopy (SEM), energy dispersive X-ray spectroscopy (EDS), and X-ray photoelectron spectra (XPS) were used to investigate the crystalline structures, surface morphologies and microstructures, and element components and their valences of the as-synthesized samples. Furthermore, planar chemical gas sensors based on the synthesized pure SnO2 and NiO/SnO2 composites were fabricated and their sensing performances to hydrogen, an important fault characteristic gas dissolved in power transformer oil, were investigated in detail. Gas sensing experiments indicate that the NiO/SnO2 composites showed much higher gas response and lower working temperature than those of pure SnO2, which could be ascribed to the formation of p-n heterojunctions between p-type NiO and n-type SnO2. These results demonstrate that the as-synthesized NiO/SnO2 composites a promising hydrogen sensing material.